COGNITIVE ABILITY, INTRINSIC MOTIVATION, AND SELF EFFICIENCY TOWARDS EMPLOYEE PERFORMANCE - Syamsuri, Abd. Rasyid; Halim, Abd.; Ikhlash, Muhammad; Setiani, Cindy; Esmeralda, Angel II P. (Pusat P2M Politeknik Negeri Batam, 2022)
This study aimed to analyze cognitive abilities, intrinsic motivation, and self-efficacy towards the employees performance of PT. Bank Danamon Sub Branch Office Sutomo, Medan. This study used quantitative methods with several tests namely classical assumption test, multiple linear regression, hypothesis testing and R2 test. Based on the results of the regression obtained the equation: Y = 0.948 + 0.425 X1 + 0.470 X2 + 0.668 X3. Partially, the tcount value of this study is 3.28 and it is known that the cognitive ability variable (X1) has a ttable of 1.70. When compared with tcount, the result was 3.28> 1.70, so it can be concluded that the cognitive ability variable (X1) has a positive and significant effect on the employee performance variable (Y). The intrinsic motivation variable (X2) has a tcount of 2.53. When compared with ttable, the results were 2.53> 1.70, so it can be concluded that the intrinsic motivation variable (X2) has a positive and significant effect on the employee performance variable (Y). The self-efficacy variable (X3) has a tcount of 4.63 and when compared with ttable the results were 4.63> 1.70, so it can be concluded that the self-efficacy variable (X3) has a positive and significant effect on the employee performance variable (Y). Simultaneously, the variables of cognitive ability, intrinsic motivation, and self-efficacy have a positive and significant influence on employee performance. This means that the hypothesis in this study is accepted, as evidenced by the value of Fcount > Ftable (13,837>2,93). Cognitive ability, intrinsic motivation, and self-efficacy have an influence on employee performance variables by 55.4%, while the remaining 44.6% was influenced by other variables not examined in this study